In-situ monitoring the structural pathway of a Ti-based alloy from metallic liquid to metallic glass - Georgarakis, Konstantinos; Stiehler, Martin E.; Hennet, Louis; Guo, Yaofeng; Antonowicz, Jerzy; Louzguine-Luzgin, Dmitri V.; Jolly, Mark R.; Andrieux, Jérôme; Vaughan, Gavin B. M.; Greer, A. Lindsay (Elsevier, 2025)
A metallic glass is formed when a molten metallic alloy is cooled rapidly enough that crystallisation is avoided. However, the way the atomic structure of the liquid converts to that of the glass is generally unknown. The main challenge is the sufficiently fast experimental acquisition of structural data in the undercooled liquid regime necessitated by the high cooling rates needed to avoid crystallisation. In the present study, using aerodynamic levitation, the Ni-free Ti-based alloy Ti40Zr10Cu34Pd14Sn2 was vitrified in-situ in a high-energy synchrotron X-ray beam while diffraction data were acquired during cooling from above the liquidus temperature Tliq to well below the glass-transition temperature Tg. The structure in the undercooled liquid regime shows an accelerated evolution. Both the local order in the short (SRO) and medium range (MRO) increases rapidly as the undercooled liquid approaches Tg, below which the amorphous structure “freezes”. Nevertheless, distinct differences between the evolution of SRO and MRO were observed. The structural rearrangements in the undercooled liquid are found to be correlated with a rapid increase in viscosity of the metallic liquid upon cooling. The new findings shed light on the evolution of the atomic structure of metallic liquids during vitrification and the structural origins of the sluggish kinetics that suppress nucleation and growth of crystalline phases.
Keywords: 40 Engineering; 4016 Materials Engineering; 51 Physical Sciences; Materials; 4016 Materials engineering; 5104 Condensed matter physics; Metallic glasses; Vitrification; Atomic structure; Levitation; Synchrotron radiation; Structure formation